Penyelesaian Perkara Investasi Online Ilegal Dalam Hukum Positif Indonesia - Beta Nur Insani; Moh Zeinudin; Miftahul Munir (JURNAL HUKUM PELITA, 2025)
This study analyzes Law Number 8 of 1999 concerning Consumer Protection related to dispute resolution methods and responsibilities that can be carried out by illegal online investment business actors. This normative research was conducted using a legislative approach, a conceptual approach, and a historical/historical approach. Settlement of illegal online investment disputes can be carried out using consumer protection mechanisms as regulated in Law Number 8 of 1999. In this case, investors are positioned as consumers who have the right to security and clarity of information. Victims can take criminal legal action by reporting to the police, or through non-litigation channels such as mediation at BPSK. However, settlement is often hampered because the perpetrators use fake identities and do not have official permission from the OJK. Therefore, synergy between consumer protection, criminal law enforcement, and supervision of financial institutions is very important to ensure justice for victims of illegal investment. The perpetrator's responsibility can be imposed through: Civil: replacing losses based on Article 1365 of the Criminal Code, Criminal: charged with fraud (Article 378 of the Criminal Code) and the ITE Law, Restitutive: returning the victim's assets through confiscation and auction mechanisms according to the TPPU Law